Formulation and Activity Test of Nanogel from Ethanol Extract of Breadfulness Leaves (Artocarpus Altilis) as A Topical Preparation for Healing Burn Wounds in Male White Rats - Fitria, Fitria; Sumaiyah, Sumaiyah; Yuandani, Yuandani (Trends in Sciences, 2025)
Breadfruit leaves (Artocarpus altilis) contain secondary metabolites that help burn wound healing, and nanogels improve drug delivery through better skin penetration. This study aims to evaluate the effectiveness of breadfruit leaf ethanol extract nanogel in healing burns in rats. Ethanol extract of breadfruit leaves was obtained by maceration using 96 % ethanol solvent, nanogels were prepared in 3 concentrations namely F1 (1.5625 %), F2 (3.125 %) and F3 (6.25 %) which were tested for physical characteristics of the preparation, stability, antibacterial activity, irritation and burn healing on rat skin. The ethanol extract of breadfruit leaf nanogel was stable for 12 weeks of storage, organoleptically good, good spreadability 5 - 6.1 cm, transmittance percentage test 92.17 - 92.98 %, and more stable at room temperature for 12 weeks of storage, pH stable for 12 weeks of storage, good viscosity between 2,970 - 3,227 cPs, centrifugation test and cycle test showed no phase separation, had antibacterial activity with an inhibition zone diameter of 9.4 to 11 mm against Staphylococcus aureus and Pseudomonas aeruginosa and did not cause irritation in rabbits. Group F2 showed a faster percentage of wound diameter reduction of 92.84 %, compared to groups F1 and F3 with a healing percentage of 81.14 and 88.91 % concentration within 21 days. Histopathologically, the calculation of the number of angiogenesis, fibroblasts and collagen using a Zeiss Primo Star microscope, Germany, F2 showed better blood vessel formation, which was as many as 14 compared to F1 and F3 with an average of 9.4 and 10 respectively. The formation of the number of fibroblast cells in F1, F2 and F3 was 95, 148 and 132 respectively. Collagen density in F1, F2 and F3 averaged 1 (< 10 %), 3 (50 - 90 %), 3 (90 - 100 %). It can be concluded that F2 has the best healing percentage compared to F1 and F3. HIGHLIGHTS Ethanol extract of breadfruit leaves and nanogel preparations of ethanol extract of breadfruit leaves have antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa bacteria which often infect human skin, especially open wounds. Nanogel of ethanol extract of breadfruit leaves with a concentration of 3.125 % (F2) provided a better healing effect on burns in mice with an average percentage of burn healing of 92.84 % on day 21, while a concentration of 6.25 % (F3) with an average percentage of burn healing of 88.91 % on day 21, and a concentration of 1.5625 % (F1) with an average percentage of burn healing of 81.14 % on day 21. GRAPHICAL ABSTRACT